5As Team obesity intervention in primary care: development and evaluation of shared decision‐making weight management tools. Issue 4 (30th June 2015) - Osunlana, A. M.; Asselin, J.; Anderson, R.; Ogunleye, A. A.; Cave, A.; Sharma, A. M.; Campbell‐Scherer, D. L.
Summary: Despite several clinical practice guidelines, there remains a considerable gap in prevention and management of obesity in primary care. To address the need for changing provider behaviour, a randomized controlled trial with convergent mixed method evaluation, the 5As Team (5AsT) study, was conducted. As part of the 5AsT intervention, the 5AsT tool kit was developed. This paper describes the development process and evaluation of these tools. Tools were co‐developed by the multidisciplinary research team and the 5AsT, which included registered nurses/nurse practitioners ( n  = 15), mental health workers ( n  = 7) and registered dieticians ( n  = 7), who were previously randomized to the 5AsT intervention group at a primary care network in Edmonton, Alberta, Canada. The 5AsT tool development occurred through a practice/implementation‐oriented, need‐based, iterative process during learning collaborative sessions of the 5AsT intervention. Feedback during tool development was received through field notes and final provider evaluation was carried out through anonymous questionnaires. Twelve tools were co‐developed with 5AsT. All tools were evaluated as either 'most useful' or 'moderately useful' in primary care practice by the 5AsT. Four key findings during 5AsT tool development were the need for: tools that were adaptive, tools to facilitate interdisciplinary practice, tools to help patients understand realistic expectations for weight loss and shared decision‐making tools for goal setting and relapse prevention. The 5AsT tools are primary care tools which extend the utility of the 5As of obesity management framework in clinical practice.